NILAI PROFIL PELAJAR PANCASILA DALAM NOVEL NAMAKU ALAM DAN RELEVANSINYA SEBAGAI BAHAN AJAR TEKS NOVEL - Khansa Hafidza; Ari Suryawati Secio Chaesar (Universitas Batanghari, 2025)
Literature learning is still not optimally implemented due to obstacles such as monotonous material delivery and the lack of student interest in literature. The selection of appropriate, relevant teaching materials that do not solely focus on academics but also highlight character education aspects can support enjoyable literature learning that aligns with national education goals. Teaching materials that include character education can be applied through the use of novels containing the values of the Pancasila Student Profile in accordance with the Merdeka Curriculum. This research aims to describe and explain (1) the values of the Pancasila Student Profile in the novel 'Namaku Alam' by Leila S Chudori; and (2) the relevance of the novel 'Namaku Alam' as teaching material for novel texts. This research employs qualitative descriptive research with the data sources being the novel 'Namaku Alam' by Leila S Chudori and informant sources. The research data consists of dialogues and quotes from novels that contain the values of the Pancasila Student Profile, as well as interview results with informants. The sampling technique used is purposive sampling. Data collection techniques employ document analysis and interviews. As for data validation techniques, it uses theory triangulation and data source triangulation. The research results show that the novel